Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1017/jfm.2016.368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of confinement in wall-bounded non-colloidal suspensions

Abstract: This paper presents three-dimensional numerical simulations of non-colloidal dense suspensions in a wall-bounded shear flow at zero Reynolds number. Simulations rely on a fictitious domain method with a detailed modelling of particle-particle and wall-particle lubrication forces, as well as contact forces including particle roughness and friction. This study emphasizes the effect of walls on the structure, velocity and rheology of a moderately confined suspension (channel gap to particle radius ratio of 20) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 52 publications
(107 reference statements)
3
41
0
Order By: Relevance
“…The analysis of the particle concentration distribution across the gap supports a two steps scenario of the instability: migration of the particles towards the cell walls followed by an instability due to the concentration gradient across the gap. Recent measurements of the first normal stresses difference [13,14] and the theory of longitudinal instability due to the first normal stresses difference [6] account reasonably for our experimental observations. More quantitative comparisons will require further measurements of the concentration across the gap as well as of the particle distribution function in order to estimate N 1 (z).…”
supporting
confidence: 85%
“…The analysis of the particle concentration distribution across the gap supports a two steps scenario of the instability: migration of the particles towards the cell walls followed by an instability due to the concentration gradient across the gap. Recent measurements of the first normal stresses difference [13,14] and the theory of longitudinal instability due to the first normal stresses difference [6] account reasonably for our experimental observations. More quantitative comparisons will require further measurements of the concentration across the gap as well as of the particle distribution function in order to estimate N 1 (z).…”
supporting
confidence: 85%
“…According to this scenario, layering should slow down the migration process, as we observed in the present study where, above φ b = 40%, the migration strain scale no longer decreases. Conversely, the numerical simulations of Gallier (2016) indicate that the particle stress (whose divergence in inhomogeneous flow drives the migration) is only slightly affected by the structuration of the suspension. From the latter observation, one would expect the migration dynamics to be unaffected by layering.…”
Section: Resultsmentioning
confidence: 95%
“…In practice, index matching and direct optical visualization require small systems. Moreover, providing experimental results for such confinement is useful to compare with numerical simulations which, limited by computation time, also investigate systems having similar sizes (Gallier (2016)). Most importantly, for gap /a > 20, previous experiments and numerical simulations both already showed that confinement has a negligible impact on macroscopic quantities such as the suspension viscosity (Maxey (2017)), but also on the fully developed concentration profiles (Snook et al (2016)).…”
Section: Resultsmentioning
confidence: 99%
“…Some experiments using more conventional rheometry find that N 1 is quite small and negative [10][11][12][13], while others report positive values [14]. Some recent studies point to the effect of polydispersity [15] and of confinement [16] which may explain these discrepancies.…”
Section: Suspension Viscositymentioning
confidence: 98%